2014
DOI: 10.1080/87559129.2014.940086
|View full text |Cite
|
Sign up to set email alerts
|

Safety Challenges Associated with Traditional Foods of West Africa

Abstract: In West Africa, varieties of agricultural produce are processed traditionally for value addition, and they significantly support food security. Nonfermented and fermented foods are important traditional foods that support dietary intake of the people and enhanced nutritional requirements and health. Throughout the subregion, there is limited large-scale industrial production of traditional foods; many of the food processing facilities are still home based or in cottage industries using rudimentary tools and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 84 publications
0
27
0
Order By: Relevance
“…L. plantarum ULAG24 also stimulated synthesis of cytokines IL10 in mice gut which is known to be anti-inflamatory, and IFNγ which has antiviral, immunoregulatory, and anti-tumour properties. These cytokines play important role as gut immunoregulators, and their induction during persistence and chronic diarrohea associated with rotaviruse and enteropthogenic E. coli in developing counties has been well documented (Azim et al, 1999;Flores et al, 2008;Oguntoyinbo, 2014). Therefore, this strain can be referred to as probiotic starter cultures with health improvement properties that include gut colonisation, pathogens inhibition and induction of immune response.…”
Section: Plantaricin Genes Strainmentioning
confidence: 94%
“…L. plantarum ULAG24 also stimulated synthesis of cytokines IL10 in mice gut which is known to be anti-inflamatory, and IFNγ which has antiviral, immunoregulatory, and anti-tumour properties. These cytokines play important role as gut immunoregulators, and their induction during persistence and chronic diarrohea associated with rotaviruse and enteropthogenic E. coli in developing counties has been well documented (Azim et al, 1999;Flores et al, 2008;Oguntoyinbo, 2014). Therefore, this strain can be referred to as probiotic starter cultures with health improvement properties that include gut colonisation, pathogens inhibition and induction of immune response.…”
Section: Plantaricin Genes Strainmentioning
confidence: 94%
“…Recently, Oguntoyinbo (2014) reported that very little attention is placed on the type of packaging used for many traditional foods in West Africa. Unhygienic and substandard packaging materials can engender easy contamination by hazardous materials, including biological, physical, and chemical hazard of well-prepared foods during preservation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, legumes are a particularly rich source of natural toxicants, including proteinase inhibitors, amylase inhibitors, metal chelates, flatus factors, hemagglutinins, saponins, cyanogens, lathyrogens, tannins, allergens, acetylenic furans, and isoflavonoid phytoalexins (Issoufou et al, 2013; Oguntoyinbo, 2014). The unfermented African oil bean seeds contain a number of anti-nutritional and /or toxic factors including saponins, alkaloids (alkaloid paucine), sterols, glycosides, and growth depressant caffeolyputrescine, but no hemagglutinins (Kar and Okechukwu, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…A clear cut was seen between the responses of countries where French and Arabic are spoken (attended by the African colleagues) and those in which English or Portuguese are the official languages (attended by the European colleagues), with the latter responding very late, if at all (despite several attempts made to get an answer), while the African colleagues were able to provide results within two weeks. Differences between the authorities and citizens asking for their advice is a global phenomenon, but also African researchers make special emphasis on the local conditions [17].…”
Section: Data Availabilitymentioning
confidence: 99%
“…As traditional food production has experienced labor ease by means of mechanization of e.g., cutting and grating processes, the production increase has not lead to a growing awareness of food safety, good manufacturing practices, and poor hygiene. Selling food that requires a certain degree of air circulations in tight-sealing plastic bags may also affect the quality by favoring the growth of microaerophilic or even anaerobial flora [17]. Since insects are traditional foodstuffs, these risks may also apply to them.…”
Section: Edible Insects In African Food Legislationsmentioning
confidence: 99%